2017
DOI: 10.1016/j.jtrangeo.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

“Cycling was never so easy!” An analysis of e-bike commuters' motives, travel behaviour and experiences using GPS-tracking and interviews

Abstract: The market for electrically-assisted cycling is growing fast. When substituting motorized travel, it could play an important role in the development of sustainable transport systems. This study aimed to assess the potential of e-bikes for low-carbon commuting by analysing e-bike commuters' motives, travel behaviour and experiences. We GPS-tracked outdoor movements of 24 e-bike users in the Netherlands for two weeks and used their mapped travel behaviour as input for follow-up in-depth interviews. Most particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 37 publications
4
56
0
1
Order By: Relevance
“…For participants who lived closer to their workplace, and in more densely populated areas, cycling was equally fast or faster than a car, especially when riding the e-bike and during rush hour. Correspondingly, in a small sample of novice e-bike users in Canada, the participants emphasised that when accounting for the time necessary for parking, the total commute time for an e-bike and a car was comparable [ 27 ], and in a Dutch study, the duration of commutes by e-bike was approximately as long as bus commutes but longer than car commutes [ 18 ]. Additionally, in a study in the San Francisco Bay Area [ 15 ], participants and cargo e-bike users emphasised that compared with driving a car during rush hour, the commute by bike was far more time reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For participants who lived closer to their workplace, and in more densely populated areas, cycling was equally fast or faster than a car, especially when riding the e-bike and during rush hour. Correspondingly, in a small sample of novice e-bike users in Canada, the participants emphasised that when accounting for the time necessary for parking, the total commute time for an e-bike and a car was comparable [ 27 ], and in a Dutch study, the duration of commutes by e-bike was approximately as long as bus commutes but longer than car commutes [ 18 ]. Additionally, in a study in the San Francisco Bay Area [ 15 ], participants and cargo e-bike users emphasised that compared with driving a car during rush hour, the commute by bike was far more time reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the feasibility of or parents’ experiences with everyday cycling; however, a US study reported that using a cargo e-bike for family transport was far more time reliable during rush hour than driving a car, and the greater mobility and freedom of travel provided by the cargo e-bike were highly valued [ 15 ]. Additionally, an intrinsic utility related to the commute by bike has been described by adult e-bike users in the Netherlands, entailing a feeling of well-being from being physically active outdoors, combined with an allowance to prepare mentally for the day ahead, or to disconnect from work on the way home in the afternoon [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive academic and societal debate about differences in techniques, the potential changes in the geographical range of cycling (e.g. Plazier et al, 2017a) and in the range of the target population (e.g. Plazier et al, 2017b;de Kruijf et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Even though less effort is needed to reach certain speeds, some physical effort is made during e-biking, as the motor assistance operates in combination with effort by the user, as shown by [28]. The physical activity, albeit reduced, is a motivator to use a pedelec [25,[29][30][31]. Ref.…”
Section: Motivators and Barriers For Bicycle And Pedelecsmentioning
confidence: 99%